156 Modeling Energy Requirement of Chinese Yellow broiler breeder hens during egg-laying period. (7th December 2018) - Gou, Z; Jiang, Z; Li, L; Lin, X; Wang, Y; Fan, Q; Zheng, C; Jiang, S
Abstract: The objective of this study is to build energy models for predicting nitrogen-corrected apparent metabolizable energy (AMEn) requirements of different categories of Chinese Yellow broiler breeder hens during egg-laying period. Data for modelling were generated from published research papers, unpublished results from our research group and some production data supplied by compaines. There are dozens of breeds of Chinese Yellow broiler breeders in China, therefore, hens were alloted into 3 categories: heavy, medium and light body weight (BW, kg). We reffered to published articles to determine coefficients of AMEn requirement for maintenance (AMEnm) and gain (AMEng) respectively. The moldels of AMEn for egg production (AMEnp) were built and then daily intake of AMEn (AMEni, kcal/d/hen) models acquired according to factorial approach that AMEni = AMEnm + AMEng +AMEnp. Heavy BW: AMEni = 101 × BW0.75 + 5.33 × average daily gain (ADG, g) + 2.55 × egg mass (EM, g/d/hen) (P < 0.001; R 2 = 0.711); medium BW: AMEni = 101 × BW 0.75 + 5.33 × ADG + 2.94 × EM (P < 0.01; R 2 = 0.586) and light BW: AMEnp = 126 × BW 0.75 + 5.33 × ADG + 1.88 × EM (P < 0.001; R 2 = 0.605). The AMEn requirments (kcal/kg diet) for each category of hens were determined with 2678, 2628 and 2583 kcal/kg for heavy, medium and light BW respectively, which are the mean values of dietary AMEn from many published articles divided into 3 categories accordingly. The AMEni requirements acquired from the models were 348, 303 and 210 kcal/d/hen for heavy, medium and light BW respectively. These models were evaluated by simulation of experiments reported in the literature, and comparison of simulated to measured requirements, which showed that models provided good adjustments. Performance trials will be conducted to further evaluate these models.